Improvements on quantum binary searching algorithm - 李慧 李春文 姜敏 (Optoelectronics letters, 2009)
In order to solve the ordered quantum database search problem, a quantum binary searching algorithm was proposed which can be used to implement the whole searching process in four steps. Considering the characteristic of quantum parallelism, this paper further improves the searching process, which can be realized in only two steps, and presents the circuit implementation. In this scheme, the number of the quantum logic gates doesn＇t increase. Moreover, the losing-solution issue in the quantum binary searching algorithm can be efficiently prevented.